Internet and cyber security governance and violation of right to privacy - Ganesan, K.; Usha., D. (International Journal of Psychosocial Rehabilitation, 2020)
To protect the rights to privacy and freedom of expression, as well as to achieve transparency, including in balancing the two rights, is not an easy task in the context of the present Internet Governance structures and practices. Internet Governance issues nowadays cover a mixture of international and national problems, commercial interests and human rights protection, national State power and transnational digital giants, and an assortment of civil society organizations and whistleblowers. The multi-stakeholder governance approach is exactly a reflection of the present complex situation, in which State authority has not been the predominant player, despite the fact that its powers continue to increase in the name of protecting national security, public order and other public interests.